GENRE DYNAMICS: MYSTERY, FANTASY, AND REALISM IN THE LITERARY TAPESTRY OF 20TH CENTURY AMERICAN CHILDREN'S - Niyazova Mokhichekhra Khayatovna; Mavlonov Azizbek Rustamovich (Web of Journals Publishing, 2023)
This article discusses significant changes in American children's literature the 20th century, with the rise and development of a variety of genres that are now essential to the canon of books for young readers. This study explores the unique characteristics, noteworthy accomplishments, and long-lasting influence of the mystery, fantasy, and realism genres on children's literature
Keywords: American children's literature, 20th century, mystery genre, fantasy genre, realism genre, traditional folktales, fairy tales, customary stories.